2018
DOI: 10.5897/ajbm2018.8523
|View full text |Cite
|
Sign up to set email alerts
|

Altruism towards others and sustainability intention of small business owners

Abstract: Though, small businesses are vital globally, they contribute to environmental and social challenges such as deforestation, pollution, use of polythene bags, poor working conditions, child labour and health hazards. Thus, it is vital to understand the concept of sustainability intention of small business owners. The purpose of this study therefore was to assess how altruism towards others influences sustainability intention of small business owners in Uganda. The study adopted a cross sectional design. A sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore, previous research shows that regular entrepreneurs do have a tendency toward altruism, presenting characteristics and acting aligned with such concerns. For instance, studies have confirmed these entrepreneurs have considerable levels of altruism (Riedo et al, 2019), which often also bears close connection to sustainability principles similarly to social entrepreneurs (Kimuli et al, 2018). In this sense, our research further confirms this altruistic trend with social entrepreneurs similarly to what other studies found (Chakraborty et al, 2021; Petrovskaya & Mirakyan, 2018), that is, the fact that social entrepreneurs are prone to altruism, but our study advances with it as our research question also investigates SEI from volunteers, which although it appears to be likely trend, it has not been properly explored by the previous studies cited above.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, previous research shows that regular entrepreneurs do have a tendency toward altruism, presenting characteristics and acting aligned with such concerns. For instance, studies have confirmed these entrepreneurs have considerable levels of altruism (Riedo et al, 2019), which often also bears close connection to sustainability principles similarly to social entrepreneurs (Kimuli et al, 2018). In this sense, our research further confirms this altruistic trend with social entrepreneurs similarly to what other studies found (Chakraborty et al, 2021; Petrovskaya & Mirakyan, 2018), that is, the fact that social entrepreneurs are prone to altruism, but our study advances with it as our research question also investigates SEI from volunteers, which although it appears to be likely trend, it has not been properly explored by the previous studies cited above.…”
Section: Discussionmentioning
confidence: 98%